Craft and science: International perspectives on archaeological ceramics - Marcos Martinón-Torres (UCL Qatar Series in Archaeology and Cultural Heritage, 2014)
Ceramics are among the most abundant materials recovered in archaeological sites. Traditionally, they have served as the main staple for archaeologists to establish chronological sequences within sites and cultural affiliations between sites. They are also a primary source for a wealth of information about past economies, social structures and ritual behaviour. In addition, ceramics preserve in their bodies the traces of countless forms of experimentation, knowledge transmission, technical ingenuity and artistic sensitivity, transcending the boundaries between art, craft and science both in their original production, and in their current study. As a sustained area of research, the study of ceramics has historically served as a prime arena for innovation, both through the pioneer application of instrumental analyses and as a core foundation and testing ground for influential archaeological theories. Inevitably, some research methods are well-established in some regions, whereas they are still emerging in others. Also the integration between science-based approaches and archaeological theory is uneven. However, emerging academic traditions, and those in less-resourced regions, should not be overshadowed by the more established paradigms. While it is impossible to keep up with all the work carried out on archaeological ceramics worldwide, it is essential that researchers continue to exchange and compare their methods, results and ideas, and that these are made available to a broader archaeological readership. This book aims to facilitate this exchange and update of information on diverse approaches to archaeological ceramics across much of the world.